Multi-mycotoxin determination in barley and derived products from Tunisia and estimation of their dietary intake. (May 2017) - Juan, C.; Berrada, H.; Mañes, J.; Oueslati, S.
Abstract: A study on raw barley and derived products (barley soup and beers) was carried out to determine the natural presence of twenty-four mycotoxins by both liquid chromatography and gas chromatography coupled to tandem mass spectrometry (MS/MS). The developed multi-mycotoxin procedure was based on both SLE and QuEChERS extraction steps. 66% of analyzed samples presented mycotoxin contamination and only one sample, which was soup of barley (6 ng/g), exceeded the maximum level (ML) established by EU for OTA (5 ng/g). Raw barley was the most contaminated matrix (62%), which concentrations ranged from 1.70 to 287.13 ng/g) and type of detected mycotoxins (DON, 15AcDON, NEO, NIV, HT2, FB1, OTA, ENA, ENA1, ENB and ENB1). DON was the most detected mycotoxin with an incidence of 56%, 29% and 23% in beer, soup of barley and barley, respectively. However, the highest levels detected were for ENA, in raw barley with 287 ng/g. In beer and soup of barley samples, the mycotoxins with highest level were 15AcDON (15.6 ng/g) and ENB1 (55.1 ng/g), respectively. Furthermore, 80% of positive soup of barley samples showed co-occurrence. No toxicological concern was associated to mycotoxins exposure for consumers. Highlights: Tunisian raw barley and barley products samples (n = 86) were investigated for 24 mycotoxins. Raw barley samples were the most contaminated matrix (n = 21). DON was the most detected mycotoxin (37%). Beer samples (56%) presented higher DON contamination than raw (23%) and soup baley (29%). No toxicological concern was associated to mycotoxins exposure for barley consumers.